Emergence of coexistence of a novel blaNDM-5-harbouring IncI1-I plasmid and an mcr-1.1-harbouring IncHI2 plasmid in a clinical Escherichia coli isolate in China - Xiaofan Zhang; Lingxia Chen; Xia Zhang; Qian Wang; Jingjing Quan; Jintao He; Hongying Pan; Xi Li (Elsevier, 2022)
Background: Co-harbouring of carbapenem and colistin resistance genes in multidrug-resistant Enterobacterales strains poses a serious public health problem. In this study, an MCR-1.1 and NDM-5 coproducing Escherichia coli strain named EC6563 was isolated and characterized. Objectives: This study aimed to characterize a clinical carbapenem-resistant E. coli isolate which co-harbours mcr-1.1 and blaNDM-5 on separate plasmids, and explored the phenotypic and genotypic characteristics of the mcr-1.1- and blaNDM-5-harbouring plasmids. Methods: E. coli isolate EC6563 was subjected to antimicrobial susceptibility testing, conjugation assay, stability of the plasmid and growth rate determination. In addition, the whole genome sequence of this strain was obtained and the genetic characteristics of the mcr-1.1- and blaNDM-5-harbouring plasmids were analyzed. Results: Carbapenem-resistant E. coli isolate EC6563 was resistant to all the tested antibiotics except tigecycline. Bioinformatic analysis confirmed that the IncHI2 plasmid carrying mcr-1.1 was highly similar to the previously reported mcr-1.1-harbouring plasmid pGDP37-4, and carried multiple drug resistance genes and the IncI1-I plasmid carrying blaNDM-5 had low similarity to the published blaNDM-5-carrying IncI1-I plasmid pEC-16-10-NDM-5. The pEC6563-NDM5 plasmid was capable of conjugation with an efficiency of 1.34 × 10−2 in a filter mating experiment. The transconjugant J53/pEC6563-NDM5 was able to be stably inherited after 12 days of passage. Conclusions: To the best of our knowledge, this is the first time that an IncHI2 plasmid carrying mcr-1.1 and an IncI1-I plasmid carrying blaNDM-5 is found to coexist in an E. coli isolate. Our research expands the known diversity of plasmids in NDM-5-producing Enterobacterales strains. Meanwhile, effective measures should be taken to prevent the spread of these plasmids.